Improving Studentsâ Reading Comprehension Using M.U.R.D.E.R Technique - Ariani, Geta (JoLLIET, 2015)
This study aims to describe (1) how M.U.R.D.E.R technique can improve studentsâ reading comprehension; (2) what may happen in the class when M.U.R.D.E.R technique is implemented in the reading class. The research was conducted at SMA N 2 Karanganyar. The research subject was the students of XI-IPA 2. The data of this research are qualitative and quantitative data. The qualitative data were collected through interview, observation, questionnaire, and photograph and were analyzed using assembling the data, coding the data, comparing the data, building interpretation, and reporting the outcomes. The quantitative data were collected through test and were analyzed using descriptive statistics. The result of the research shows that: (1) M.U.R.D.E.R technique could improve studentsâ reading comprehension. The mean score of pre-test (61.35) improved to 71.95 in post-test 1 and to 78.08 in post-test 2; (2) the students were more active and communicative. They had more courage to share their ideas to their partner.